2000
DOI: 10.1068/a3222
|View full text |Cite
|
Sign up to set email alerts
|

Residential Mobility in a Constrained Housing Market: Implications for Ethnic Populations in Germany

Abstract: The rates of residential mobility in Germany are significantly lower than in the United States, and even lower than in some other European countries. The lower mobility rates can be viewed as outcomes of a ‘tight’ housing market. It can be hypothesized that, because ethnic minorities (‘foreigners’ in German terminology) have lower incomes and face discrimination, they are likely to be more constrained than the native-born German population, and so have even lower mobility rates. The authors use data from the G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 12 publications
1
23
0
2
Order By: Relevance
“…Así, la movilidad residencial aparece como indicador de las constricciones en el mercado de la vivienda. En este sentido, no se encuentra una menor movilidad residencial entre los extranjeros (Clark y Drever, 2000), aunque esto no significa una movilidad hacia viviendas de mejor calidad. Al mismo tiempo, esta movilidad es muchas veces interpretada como elemento de éxito social cuando ésta permite al inmigrante acceder a espacios étnicamente indiferenciados (Simon, 1998).…”
Section: Marco Teóricounclassified
See 1 more Smart Citation
“…Así, la movilidad residencial aparece como indicador de las constricciones en el mercado de la vivienda. En este sentido, no se encuentra una menor movilidad residencial entre los extranjeros (Clark y Drever, 2000), aunque esto no significa una movilidad hacia viviendas de mejor calidad. Al mismo tiempo, esta movilidad es muchas veces interpretada como elemento de éxito social cuando ésta permite al inmigrante acceder a espacios étnicamente indiferenciados (Simon, 1998).…”
Section: Marco Teóricounclassified
“…En general se apunta la mayor movilidad de los extranjeros, en especial en etapas iniciales de su proceso migratorio como se ha corroborado para el caso de España (Recaño, 2002;García-Coll, 2005). A pesar de ello, al controlarse una variable fundamental como la económica, en algunos casos se indica una menor propensión a cambiar de domicilio y, por tanto, ajustar su condición económica con la habitacional (Clark y Drever, 2000).…”
Section: Marco Teóricounclassified
“…The market is predominantly rental, and entry to the homeowner sector occurs later than in other European countries ( Borsch-Supan 1993;Deurloo, Dieleman, and Clark 1997). Despite these differences, studies of mobility in Germany have shown the applicability of the general model of mobility (Frick 1996;Clark and Drever 2000), which indicates that the role of age and space are as important in mobility behavior in the German housing market as they are in the United States. That research also shows that there is little variation in mobility rates by citizenship even when there are appropriate controls for age and socio-economic status (Clark and Drever 2000).…”
Section: Previous Work and The Research Contextmentioning
confidence: 99%
“…Despite these differences, studies of mobility in Germany have shown the applicability of the general model of mobility (Frick 1996;Clark and Drever 2000), which indicates that the role of age and space are as important in mobility behavior in the German housing market as they are in the United States. That research also shows that there is little variation in mobility rates by citizenship even when there are appropriate controls for age and socio-economic status (Clark and Drever 2000). However, it does not rule out the possibility that immigrants are circulating within poor quality housing.…”
Section: Previous Work and The Research Contextmentioning
confidence: 99%
“…However, household income factor is substantially considered the most important determinant of residential crowding [8]. In most European countries such as Germany, foreigners and non-native population are more likely to live in overcrowding housing than native population [9]. A person per room is usually used as a basic indicator for measuring overcrowding.…”
Section: Introductionmentioning
confidence: 99%